(untitled) (Research, Society and Development, 2023)
The objective of the present work was to evaluate the performance of Nile tilapia larvae fed with increasing levels of poultry liver hydrolysates. 700 two-day-old larvae were used, distributed in 28 boxes (40 liters), in a completely randomized design with seven treatments and four replications. The treatments consisted of diets with different inclusions of poultry liver hydrolysates: 0 (control), 2, 4, 6, 8, 10 and 12% in isoprotein diets (38% CP). Feeding was carried out six times a day (8; 10; 12; 14; 16 and 18 h). There was no influence of the hydrolyzate on the final weight, final length, final biomass, condition factor and survival of the larvae. Larvae that received diets with 4 and 6% hydrolyzate showed greater standardization in animal weight. It is recommended to use at least 4% of poultry liver protein hydrolyzate, providing greater uniformity of Nile tilapia larvae.